2021
DOI: 10.1007/s40123-021-00343-4
|View full text |Cite
|
Sign up to set email alerts
|

Short-term Evaluation of Negative Pressure Applied by the Multi-Pressure Dial System to Lower Nocturnal IOP: A Prospective, Controlled, Intra-subject Study

Abstract: This article is published with digital features, including a summary slide, to facilitate understanding of the article. To view digital features for this article go to

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 24 publications
4
9
0
Order By: Relevance
“…Further, there was no evidence of rebound IOP spikes following the application of negative pressure across all test runs. The results of this study confirm that controlled application of periocular negative pressure leads to a reduction in IOP, supporting the results of prior clinical studies [ 6 , 7 , 10 ] that reported a reduction in IOP with the MPD system. Collectively, the decrease in IOP observed in the absence of pressure changes in the retro-orbital tissue indicates that the MPD system is capable of favorably modifying the translaminar pressure difference, a pressure differential shown to be important in the pathogenesis of glaucoma [ 11 – 14 ].…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…Further, there was no evidence of rebound IOP spikes following the application of negative pressure across all test runs. The results of this study confirm that controlled application of periocular negative pressure leads to a reduction in IOP, supporting the results of prior clinical studies [ 6 , 7 , 10 ] that reported a reduction in IOP with the MPD system. Collectively, the decrease in IOP observed in the absence of pressure changes in the retro-orbital tissue indicates that the MPD system is capable of favorably modifying the translaminar pressure difference, a pressure differential shown to be important in the pathogenesis of glaucoma [ 11 – 14 ].…”
Section: Discussionsupporting
confidence: 89%
“…The IOP-lowering results demonstrated in this present study align with the results reported in prior clinical studies that have evaluated the IOP-lowering ability of the MPD [ 6 , 7 , 10 ]. In both subjects in the present study, an increase in the programmed level of negative pressure within the goggles corresponded to an increased reduction in IOP.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations